Nicolaas van Wijk (1880-1941) : Slavist, linguist, philanthropist - Hinrichs, Jan Paul (Studies in Slavic and general linguistics, 2006)
Nicolaas van Wijk (1880-1941) was the founder of Slavic studies in the Netherlands and one of the greatest Slavists in general. This book describes for the first time how a scholar of the Dutch language, whose etymological dictionary of the Dutch language is still considered the best of its kind, was appointed in 1913 to the newly created Chair in Slavic languages at Leiden University and built up a tremendous reputation for himself in Eastern Europe. Van Wijk's relations with his famous teacher, the linguist C.C. Uhlenbeck, are followed attentively, as is his postgraduate apprenticeship in Le.